Yield Improvement and Genotype × Environment Analyses of Peanut Cultivars in Multilocation Trials in West Africa. Issue 6 (1st November 2014) - Narh, Stephen; Boote, Kenneth J.; Naab, Jesse B.; Abudulai, Mumuni; M'Bi Bertin, Zagre; Sankara, Philippe; Burow, Mark D.; Tillman, Barry L.; Brandenburg, Rick L.; Jordan, David L.
ABSTRACT: Yield trials are used in plant breeding programs to evaluate the yield potential and stability of selected lines. The objectives of this study were to evaluate yield potential, genotype × environment interactions, and stability of peanut genotypes for the savannah region of West Africa. Twenty peanut ( Arachis hypogaea L.) genotypes were tested at two sites in Ghana and two sites in Burkina Faso in 2010 and 2011. The experimental design was a randomized complete block design with three replicates. Genotype, location, and genotype × environment interactions were highly significant, indicating genetic variability among genotypes across changing environments. Stability analyses showed that genotypes ICGV‐IS 96814, ICGV (FDRS)‐20 × F‐MIX 39, Gusie Balin (92099), ICGV‐IS 92093, and ICGV‐IS 92101 had broad adaptability, with above‐average yield across sites and a regression coefficient close to 1.0. Genotype ICGV‐IS 96814 produced the highest pod yield (1760 kg ha −1 ) across all environments and had a regression coefficient close to unity ( b = 1.06). Therefore, genotype ICGV‐IS 96814 is less responsive to varied environmental and soil conditions. However, the released cultivar Nkatesari was considered equivalent in some respects because it had pod yield equal to ICGV‐IS 96814 but with a higher regression coefficient. High‐yielding cultivars, mostly from ICRISAT‐derived crosses, yielded nearly 80% more than the three farmer check cultivars TS 32–1, Doumbala, and Chinese, which had pod yields from 890 to 980 kg ha −1 . The higher‐yielding cultivars had longer life cycle, greater leaf spot resistance, and higher partitioning than the farmer check cultivars.